2014
DOI: 10.1063/1.4898066
|View full text |Cite
|
Sign up to set email alerts
|

Phonon scattering in graphene over substrate steps

Abstract: We calculate the effect on phonon transport of substrate-induced bends in graphene. We consider bending induced by an abrupt kink in the substrate, and provide results for different step-heights and substrate interaction strengths. We find that individual substrate steps reduce thermal conductance in the range between 5% and 47%. We also consider the transmission across linear kinks formed by adsorption of atomic hydrogen at the bends and find that individual kinks suppress thermal conduction substantially, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
(28 reference statements)
2
14
0
Order By: Relevance
“…The presence of sp hybridization in those structures induced the existence of high-frequency vibration modes occurred between 60 THz and 70 THz [29]. This is similar to the previously predicted phonon spectra of α-, β-, γand 6,6,12-graphyne [30]. The result of phonon spectrum shows that the four structures are all stable and reliable.…”
Section: Phonon Dispersionsupporting
confidence: 85%
“…The presence of sp hybridization in those structures induced the existence of high-frequency vibration modes occurred between 60 THz and 70 THz [29]. This is similar to the previously predicted phonon spectra of α-, β-, γand 6,6,12-graphyne [30]. The result of phonon spectrum shows that the four structures are all stable and reliable.…”
Section: Phonon Dispersionsupporting
confidence: 85%
“…• bending we find the minimum ROC close to 10Å, which are close to the previous results [30]. We also perform single hydrogen adsorption calculations on curved graphene for 90…”
Section: Fig 6 Evolution Of Generations During the Hydrogenation Ofsupporting
confidence: 57%
“…The lengths of the curved parts across the step are chosen so as to remove the tensile stress after hydrogenation. For different interaction strengths, which correspond to different substrates, ROC is found to be in the range between 13.5Å and 3.3Å, where the step height is kept as 10Å [28,30]. In Figs.…”
Section: Fig 6 Evolution Of Generations During the Hydrogenation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[12][13][14][15][16][17][18] Recently, it was shown that other two-dimensional materials can also be stable and that they widen the potential of two-dimensional materials for applications. [19][20][21][22] Of particular importance are graphene-like carbon allotropes, called graphyne structures composed of one-atom-thick sheets of carbon atoms but containing sp carbon bonds in addition to sp 2 hybridized bonds [23][24][25] (see Fig.…”
mentioning
confidence: 99%